Temferon an ex-vivo genetically modified cell therapy aiming to fill the gaps for solid tumor immunotherapy. Issue 9 (2020) - Mazzoleni, Stefania; Gentner, Bernhard; Brambilla, Valentina; Magnani, Tiziana; Ciceri, Fabio; Finocchiaro, Gaetano, Luigi Naldini; Russo, Carlo
No abstract available